“Cuatro vacas escuálidas pastando sobre ricos aluviones nada le producen a la nación”: Minería, agricultura y conflicto en el Nordeste Antioqueño (1930-1950) - Henao, Diana; Campuzano, Lorena (Historia Agraria de América Latina, 2020)
This article analyzes the conflicts between miners and farmers in Northeastern Antioquia between 1930 and 1950 to understand the problematic coexistence of ideas of public and private ownership of land and gold and the role of the state in regulating them. In the agrarian literature about Colombia, scholars argue that fake mining claims became a mechanism to hoard large extensions of land. To test this hypothesis, we study Colombian mining and land legislation alongside conflicts between farmers and miners that rest in the Archivo Histórico de Antioquia. Rather than a problem of land grabbing, the conflicts between mining and agriculture reveal that the antioqueño mining tradition of mazamorreros and the promotion of frontier colonization through colonos were in stark contradiction with the new agricultural and mining uses of natural resources and the model of regional development after the great depression. Since the laws protected both, mazamorreros and colonos, and mining and farming entrepreneurs, the access to natural resources became a source of conflict in places were mining and agriculture coexisted.
Keywords: Minería; Nordeste Antioqueño (Colombia); agricultura; conflictos; leyes mineras; nación

Cattle Ranching in Colombia: A Monolithic Industry? - Campuzano, Lorena; Angel, Natalia Triana; Burkart, Stefan (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2022)
This article analyzes literature on the history of cattle ranching and agricultural innovation adoption in Colombia to understand how livestock production systems have evolved from the 1950s until today. Departing from new scholarship that has questioned the idea that cattle ranching has been only a land-grabbing strategy dominated by few elites, this article focuses on the adoption of improved pastures and the role of key institutions such as the CIAT on the transformation of practices and the shortcomings of technification. It shows that Colombia has had big transformations with the introduction of improved pastures, particularly Brachiaria, but these transformations did not translate into a radical change in the dominant extensive livestock production systems. Instead of promoting intensification, the adoption of Brachiaria has allowed producers to expand more, often resulting in large deforestation.  One of the main contributions of this article is the analysis of economic, developmentalist, and institutional reports that are not often used to construct historical analysis. It can also serve to scholars interested on adoption of agricultural techniques.
Keywords: Brachiaria; CIAT; agricultural practices; cattle ranching; livestock; technology adoption

Improved pastures and some challenges of agricultural innovation adoption - Triana Ángel, Natalia; Campuzano, Lorena; Burkart, Stefan (Bioversity International and the International Center for Tropical Agriculture, 2022)
Since the 1960s, but more intensely since the 1980s, the factors affecting agricultural innovation adoption in the so-called developing world have puzzled scholars and development institutions. Although early studies recognised that adoption is affected not only by the promise of economic profitability but also by other attributes of the innovation, such as compatibility, complexity, trialability, and observability, economic analysis that barely touched upon sociological factors or the non-contingent character of extension programmes dominated the literature until recent years. Scholars and institutions have analysed both external factors such as credit constraints, risk, and information or internal constraints such as farm size, farmer behaviour, and land tenure patterns, showing how these factors affect agricultural innovation adoption. Yet, even when constraints are lifted or improved, adoption does not seem to increase in overall terms. To explain so, new constraints have been researched, such as gender, age, and belonging to a social network but the answer is still elusive. This study reviews and summarises evidence on experiments of agricultural innovation adoption, particularly those related to improved pastures and forage seeds in the Global South. We found that, first, farmer’s social and cultural constraints must be properly mapped to explain, more in depth, the limiting factors to diffusion and the shortcomings of adoption incentives. Second, we found that perfectible transference strategies lay at the core of agricultural technology adoption, and thus we aim to amplify the debate onto how to map societal constraints and how, if so, new narratives and mechanisms should be put in place to achieve more successful innovation processes.